Clinical Sensitivity and Specificity of Meconium Fatty Acid Ethyl Ester, Ethyl Glucuronide, and Ethyl Sulfate for Detecting Maternal Drinking during Pregnancy. (6th January 2020) - Himes, Sarah K; Dukes, Kimberly A; Tripp, Tara; Petersen, Julie M; Raffo, Cheri; Burd, Larry; Odendaal, Hein; Elliott, Amy J; Hereld, Dale; Signore, Caroline; Willinger, Marian; ,
Abstract: BACKGROUND: We investigated agreement between self-reported prenatal alcohol exposure (PAE) and objective meconium alcohol markers to determine the optimal meconium marker and threshold for identifying PAE. METHODS: Meconium fatty acid ethyl esters (FAEE), ethyl glucuronide (EtG), and ethyl sulfate (EtS) were quantified by LC-MS/MS in 0.1 g meconium from infants of Safe Passage Study participants. Detailed PAE information was collected from women with a validated timeline follow-back interview. Because meconium formation begins during weeks 12–20, maternal self-reported drinking at or beyond 19 weeks was our exposure variable. RESULTS: Of 107 women, 33 reported no alcohol consumption in pregnancy, 16 stopped drinking by week 19, and 58 drank beyond 19 weeks (including 45 third-trimester drinkers). There was moderate to substantial agreement between self-reported PAE at ≥19 weeks and meconium EtG ≥30 ng/g (κ = 0.57, 95% CI 0.41–0.73). This biomarker and associated cutoff was superior to a 7 FAEE sum ≥2 nmol/g and all other individual and combination marker cutoffs. With meconium EtG ≥30 ng/g as the gold standard condition and maternal self-report at ≥19 weeks' gestation as the test condition, 82% clinical sensitivity (95% CI 71.6–92.0) and 75% specificity (95% CI 63.2–86.8) were observed. A significant dose–concentration relationship between self-reported drinks per drinking day and meconium EtG ≥30 ng/g also was observed (all P < 0.01). CONCLUSIONS: Maternal alcohol consumption at ≥19 weeks was better represented by meconium EtG ≥30 ng/g than currently used FAEE cutoffs.